Use of biologics to treat relapsing and/or refractory polyarteritis nodosa: data from a European collaborative study. (10th June 2022) - Hadjadj, Jérome; Canzian, Alice; Karadag, Omer; Contis, Anne; Maurier, François; Sanges, Sébastien; Sartorelli, Silvia; Denis, Laure; de Moreuil, Claire; Durel, Cécile-Audrey; Durupt, Stéphane; Jachiet, Marie; et al.
Abstract: Objectives: To describe the effectiveness and safety of biologics for the treatment of relapsing and/or refractory polyarteritis nodosa (PAN). Methods: A retrospective European collaborative study was conducted in patients with PAN who received biologics for relapsing and/or refractory disease. Results: Forty-two patients with PAN received a total of 53 biologic courses, including TNF-α blockers in 15 cases, rituximab (RTX) in 18 cases, tocilizumab (TCZ) in 10 cases and other biologics in 10 cases. TNF-α blockers and TCZ were mainly used for refractory diseases whereas RTX was mainly initiated for relapsing disease. After a median follow-up of 29 (8–50) months, remission, partial response, treatment failure and treatment discontinuation due to severe adverse events occurred in, respectively, 40%, 13%, 40% and 7% of patients receiving TNF-α blockers, 50%, none, 30% and 20% of TCZ recipients, and 33%, 11%, 56% and none of the RTX recipients. No remission was noted in patients treated with other biologics. Severe adverse events were observed in 14 (28%) patients without significant differences between the three biologics, leading to early biologics discontinuation in only three cases. Conclusion: These results suggest that TCZ may be effective in relapsing and/or refractory PAN. Our data warrant further study to confirm these findings.